2022
DOI: 10.1073/pnas.2212004119
|View full text |Cite
|
Sign up to set email alerts
|

Lactate supply overtakes glucose when neural computational and cognitive loads scale up

Abstract: Neural computational power is determined by neuroenergetics, but how and which energy substrates are allocated to various forms of memory engram is unclear. To solve this question, we asked whether neuronal fueling by glucose or lactate scales differently upon increasing neural computation and cognitive loads. Here, using electrophysiology, two-photon imaging, cognitive tasks, and mathematical modeling, we show that both glucose and lactate are involved in engram formation, with lactate supporting long-term sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Nonetheless, the lactate shuttle from astrocytes to neurons is critical for energy production to support normal synaptic function (Li and Sheng, 2022; Cheng et al, 2022). Importantly, recent evidence has shown that for prolonged cognitive loads, the use of lactate may be indispensable compared to glucose, suggesting that prevention of cognitive decline as seen in dementia, is dependent on the TCA cycle (Dembitskaya et al, 2022). To test this in AD-hiN vs. WT/isogenic-hiN, we supplied isotopically-labeled C 13 -lactate as the sole source of energy to hiN cultures for metabolic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the lactate shuttle from astrocytes to neurons is critical for energy production to support normal synaptic function (Li and Sheng, 2022; Cheng et al, 2022). Importantly, recent evidence has shown that for prolonged cognitive loads, the use of lactate may be indispensable compared to glucose, suggesting that prevention of cognitive decline as seen in dementia, is dependent on the TCA cycle (Dembitskaya et al, 2022). To test this in AD-hiN vs. WT/isogenic-hiN, we supplied isotopically-labeled C 13 -lactate as the sole source of energy to hiN cultures for metabolic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytic glycogen, a precursor of lactate, is the only endogenous fuel reserve for energy management during metabolically intensive or stressed conditions [42][43][44] . Astrocytic glycogen reserve is dynamically maintained through glycogenesis (via glycogen synthase) and glycogenolysis (via glycogen phosphorylase) 45,46 and is further metabolized during a metabolic demand from active neurons to generate lactate and therefore supplement such active neurons with additional energy to maintain functionality 15,27,28 . This process starts when evoked synaptic activity causes glutamate release at cortical synapses that in turn triggers astrocytic lactate release 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal activity and astrocytic support to sustain neuronal activity requires both glucose and glycogen consumption and is energy intensive even for a healthy brain 15 . The energy consumption during ischemia coupled with lactate release following whisker stimulation could serve in part to support the transition of astrocytes to their protective reactive state that in turn could potentially continue supporting the cortex even beyond the 2h time protection window.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, research on brain metabolism and bioenergetics has emerged and attracted a significant amount of attention over the last two decades. Glucose and lactate are the main energy substrates for the brain [ 14 , 242 , 243 ]. A metabolic characteristic of patients with AD is diminished cerebral glucose metabolism characterized by a decreased capacity to uptake and oxidize glucose, signaling dysregulated brain bioenergetics [ 244 , 245 , 246 , 247 , 248 ].…”
Section: The Role Of Mitochondrial Function In Multiple Diseasesmentioning
confidence: 99%
“…Furthermore, like skeletal muscle, the brain possesses a lactate shuttle key to brain bioenergetics [ 243 ]. Although glucose historically has been thought to be the main fuel for the brain, it is now well known that lactate is a key fuel for neurons, possibly the preferred fuel for the brain [ 242 , 243 , 258 , 259 ], and essential for long–term memory [ 260 , 261 ]. In skeletal muscle, the discovery of the lactate shuttle by Dr. George Brooks was instrumental in understanding skeletal muscle glucose and intermediary metabolism [ 14 ].…”
Section: The Role Of Mitochondrial Function In Multiple Diseasesmentioning
confidence: 99%